Pendidikan Kesehatan Melalui Penyuluhan Terkait Perawatan Tali Pusat Pada Bayi Baru Lahir Di Puskesmas Pembantu Golodukal - Padeng, Eufrasia Prinata; Laput, Dionesia Ocatviani; Dehamur, Oktaviani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
ABSTRACT Umbilical cord care is very important in understanding by mothers who have newborns. The incidence of infection in newborns in Indonesia is the second leading cause of death after asphyxia neonatorum. Most newborn infections are tetanus neonatorum which is transmitted through the umbilical cord, therefore it is very important to know how to care for the umbilical cord. This service aims to provide counseling to TM III pregnant women regarding proper and correct umbilical cord care practices so that infection does not occur. The method used in this service is counseling with the help of leaflets and slide shares (power point). The result of this dedication is that pregnant women understand and understand about proper and correct umbilical cord care. Keyword : Counseling, Pregnancy, Umbilical Cord,